Comparison of Local Load Influence on Crack Evolution of Coal and Briquette Coal Samples - Hongbao Zhao; Tao Wang; Huan Zhang; Ziqiang Wei (Advances in Civil Engineering)
Taking raw coal and briquette coal samples with preset center holes as research objects, this paper makes a systematic analysis and research of crack evolution laws of the two different coal samples under the local load. The results show that the raw coal and briquette coal samples are different mainly in number, dimension, and complexity of the internal microstructures, so it is not right to replace raw coal with briquette coal when performing observational study of the crack evolution of microstructures; under the effect of local load, local property, randomness of crack initiation position, and crack initiation stress of raw coal samples are greater than those of briquette coal samples; law of instantaneous maximum effective cut-through rate of raw coal samples is more complex than that of briquette coals; under the effect of uniformly distributed load, end effect factor Fe, sample microstructure influencing factor Fs, and preset center hole factor Fh are the major factors influencing crack growth, among which the amplified end effect factor Fe and sample microstructure influencing factor Fs are dominant factors; under the effect of local load, local load influencing factor Fp, end effect factor Fe, sample microstructure influencing factor Fs, and preset center hole factor Fs are the major factors influencing crack growth, among which the local load influencing factor Fp, end effect factor Fe, and sample microstructure influencing factor Fs are dominant factors. Compared with briquette coal samples, raw coal samples are more sensitive to influencing factors, such as local load influencing factor Fp, end effect factor Fe, sample microstructure influencing factor Fs, and preset center hole factor Fh, and can aggravate the influence of these factors on the crack growth; the paper also puts forward a method for describing local load based on a coupling mechanical model of uniaxial compression and local shear.